Phenotypic Adaptations in Pasteuria spp. Nematode Parasites - Ciancio, Aurelio (Society of Nematologists, 1995)
The endospore and central core diameters of 69 isolates of Pasteuria spp. showed a relationship with the body wall thickness of their corresponding host nematodes. A relationship was also observed when cuticle and hypodermis layer data were derived from transmission electron microscopy micrographs. Principal component analysis and hierarchical cluster analysis based on endospore and central core diameters and host nematode body wall thickness delineated six distinct groups. Five groups included nematode species of distinct taxa. Endospore morphometric diversity appears to be the result of an evolutionary adaptation that occurred during host nematode speciation related to the forces acting on adhering endospores and(or) to the host cuticle penetration phase. On this basis, the validity of endospore morphometrics and host taxonomy as significant parameters in discriminating Pasteuria species is questioned.